Effect of Tax Planning, Deferred Tax Expense and Company Size Against Profit Management (Empirical Study on Manufacturing Companies Listed on IDX 2015-2019) - Arni Karina; Harum Herdiyanti (Jurnal Ilmu Manajemen dan Ekonomika, 2020)
This study uses quantitative methods that aim to analyze the effect of tax planning, deferred tax expense and company size on profit management in 13 manufacturing companies listed on the Indonesia Stock Ex-change. The results of this study show that tax planning and deferred tax expense affect profit manage-ment, then the size of the company has not been shown to have an effect on profit management. The results of this study show that tax planning is a way of regulating how much profit is reported it is indicated that there are profit management practices that signal about management regulates pseudo-profit reporting while deferred tax burdens provide indications that there are differences between accounting standards and tax regulations. Management can use this as one of the instruments for carrying out profit management.